Penetration of Smart Housing as an Integral Part of Intelligent Buildings into Urban Areas of Developing Countries - GhaffarianHoseini, AmirHosein; Dahlan, Nur Dalilah; GhaffarianHoseini, Ali; Nastaran, Makaremi‎ (2011)
Due to the penetration of modernization based upon advanced technologies within developing countries, intelligent buildings are deemed to be gradually growing within their urban areas. On the other hand, smart housing as a major constituent of intelligent buildings is believed to become the prominent choice of population rather than conventional housing. Hence, this research theorizes the significant role of intelligent buildings as a fundamental issue in housing development schemes. Thereby, this study scrutinizes the essence of smart housing as a part of intelligent building design development for elucidating its strengths and weaknesses for the context of third world countries. On the contrary, the study explores the essence of vernacular built environments in order to present the profound characteristics of built environments designed and built according to the social, cultural and environmental attributes of regions. Consequently, the study argues that the environmental and socio-cultural features of local regions as influential parameters towards the enhancement of sustainability and quality of life must be highly considered in the design process of smart housing.